The Montreal Cognitive Assessment (MoCA) as a cognitive screen in addiction health care: A validation study for clinical practice. (2nd January 2019) - Bruijnen, Carolien J. W. H.; Jansen, Mandy; Dijkstra, Boukje A. G.; Walvoort, Serge J. W.; Lugtmeijer, Selma; Markus, Wiebren; De Jong, Cor A. J.; Kessels, Roy P. C.
ABSTRACT: Objective: The current study assessed the criterion validity of the Montreal Cognitive Assessment (MoCA) as a short cognitive screen for use in addiction health care. Method: Eighty-two patients were assessed with two parallel versions of the MoCA; at intake (baseline) and directly preceding an extensive neuropsychological assessment (NPA) approximately 8 weeks later (follow-up). Results: Of all included patients, 54.9% were classified as having substance-induced neurocognitive disorder. The most common primary substance of abuse was alcohol (70.7%). The criterion validity was determined predictively and concurrently, and sensitivities of .56 and .67 and specificities of .62 and .73 were found, respectively. Conclusion: While the MoCA is an adequate screen when administered at the same time as the NPA, the predictive validity of administering this cognitive screen at intake is limited. Furthermore, the relation between MoCA domain scores and the performance on their corresponding cognitive domain in the NPA is more reliable when the MoCA is administered at the same time as the NPA. While the MoCA can be used to screen for cognitive impairments in patients in addiction health care, the instrument's sensitivity is not optimal, which should be taken into account when interpreting results.